IMPLEMENTATION OF TEACHERS’ PERFORMANCE APPRAISAL DEVELOPMENT (TPAD) AND ITS EFFECTS ON TEACHING AND LEARNING ACTIVIVITIES IN KIMILILI SUBCOUNTY, BUNGOMA COUNTY KENYA - Dr. Masika Erastus K (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of this study was to investigate the implementation of teachers’ performance appraisal and development (TPAD) and its effects on teaching and learning activities in Kimilili sub county. Thus 10 schools were sampled for the study from a cluster of schools within Kimilili municipality. Stratified sampling technique was used to sample 3 boys’ boarding schools, 3 girls’ boarding schools and 4 mixed day secondary schools. Simple random sampling technique was used to sample 2 male teachers and 2 female teachers from each school on equal gender basis. The total sample size therefore were 40 respondents. Quantitative research design was used in the study where descriptive survey method was employed. Data was collected using a questionnaire. Data was then analyzed through descriptive statistics and presented in tables of frequencies and percentages. The qualitative data was summarized and analyzed thematically. The findings of the study revealed that the TPAD tool had enhanced teachers’ professional record keeping and time management. However, there were inconsistencies in lesson plan organization, self-rating, appraising challenges, teacher stagnation and lack of commitment and confidence among teachers. Among the key recommendations of the study were: review of TPAD to address the inconsistences highlighted in the study such as improvement in lesson observation, self-rating, training of appraisers in education appraising, promotion of teachers and instilling confidence among teachers on the working of the tool. The recommendations of this study may inform the teachers’ employer on challenges facing teachers as they handle TPD amid increased workload pressure and limited time.